The effect of semantic mapping technique on technical vocabulary mastery for Midwifery students - Erikson Saragih (Studies in English Language and Education, 2019)
This study was conducted to test whether Semantic Mapping Technique affects midwifery students’ technical vocabularies at the University of Prima Indonesia. Semantic Mapping is a technique of visual for the expansion of vocabularies and knowledge extension by displaying in words of categories related to each other. The total of 40 midwifery students in the academic year of 2018/2019 was taken as the research samples by applying two groups for pre-test and post-test experimental research design. The experimental group was taught by Semantic Mapping Technique while the control group was taught by conventional teaching technique of vocabulary. The research data were then analyzed using T-test. In this research, a multiple-choice test was used as the research instrument for collecting data. Both the experimental and control groups were asked to answer 50 test items in Pre-test and Post-test. The research data were then analyzed statistically by using T-test formula with the assistance of the SPSS program. The study revealed that the value of T-observed (4.41) was higher than the value of T-table (2.02) at the level of significance 0.05 with the degree of freedom (df) 40. It means that the alternative hypothesis stating that Semantic Mapping technique has a significant effect on midwifery students’ technical vocabularies is significantly accepted. By so doing, this technique can be considered to be used to increase students’ vocabularies.